Macroeconomic Indicators and Market Index Interactions in the United States: An Empirical Analysis - Abdullah, Ahmad Monir; Rithuan, Syahidah Hanis Meor; Abdullah, Hamdy (International Journal of Energy Economics and Policy, 2026)
This study investigates the dynamic interactions among the major United States (US) equity indices (NYSE, NASDAQ, and S&P 500), key macroeconomic indicators (Gross Domestic Product and Consumer Price Index), and West Texas Intermediate (WTI) crude oil prices over 2005 - 2024. Using descriptive statistics, correlation analysis, and Wavelet Transform Coherence (WTC), the research captures both linear relationships and time–frequency comovements across economic regimes, including the 2008 Global Financial Crisis, the COVID-19 pandemic, and the post-pandemic recovery. The results show strong coherence among the equity indices but weak and unstable linkages with macroeconomic fundamentals, especially GDP. WTI demonstrates persistent medium- to low-frequency coherence with CPI and equity indices during crisis periods, highlighting its role as a major macro-financial transmission channel. These findings reveal that US financial markets have become increasingly decoupled from real-sector performance while remaining sensitive to energy-price shocks and inflation dynamics. By applying a continuous wavelet approach to a long-horizon, multi-indicator dataset, this study provides a richer view of how systemic events reshape market–macro relationships. The evidence offers new insights for policy formulation, portfolio diversification, and risk management, underscoring the need for frequency-sensitive, nonlinear frameworks for analysing macro-financial interdependence.